Marine antimicrobial peptide arenicin adopts a monomeric twisted β‐hairpin structure and forms low conductivity pores in zwitterionic lipid bilayers. Issue 2 (16th February 2018) - Sychev, Sergei V.; Sukhanov, Stanislav V.; Panteleev, Pavel V.; Shenkarev, Zakhar O.; Ovchinnikova, Tatiana V.
Abstract: Arenicins are 21‐residue β‐hairpin antimicrobial peptides (AMPs) isolated from the marine lugworm Arenicola marina [Ovchinnikova et al., FEBS Lett. 2004;577:209–214]. The peptides have a high positive charge (+6) and display a broad spectrum of antimicrobial activities against bacteria and fungi. Arenicins adopt the monomeric highly twisted β‐hairpin in water or planar β‐structural dimers in anionic liposomes and detergent micelles. Until now, the interaction of cationic β‐structural AMPs with zwitterionic phospholipid bilayers mimicking eukaryotic membranes is not well understood. To study the structural basis of arenicins activity against eukaryotic cells, we investigated arenicin‐2 in the solvents of low polarity (ethanol, 4% dioxane) and in zwitterionic soybean PC and PC/PE liposomes by CD and FTIR spectroscopy. It was shown that arenicin‐2 adopted the twisted β‐hairpin structure in all the environments studied. Measurements of the Trp fluorescence and H→D exchange in soybean PC liposomes and boundary potential in the planar DPhPC bilayers confirmed the partitioning of the arenicin‐2 monomers into interfacial region of the zwitterionic membranes. The low‐conductivity (0.12 nS) arenicin‐2 pores were detected in the DPhPC bilayers. The lifetime of the open state (up to 260 ms) was significantly longer than lifetime of low‐conductivity (0.23 nS) pores previously described in partially anionic membranes (44 ms). The formation of narrow arenicin‐2 pores without disruption of the membrane was discussed in the light of the disordered toroidal pore model previously proposed for β‐structural AMPs [Jean − Francois et al. Biophys. J. 2008;95:5748 − 5756]. A novel non‐lytic mechanism of the arenicin‐2 action was proposed. Abstract :